(untitled) (Scientific journal of the Fergana State University, 2024)
The problem of developing the creative competence of future educators through the modernization and content improvement of the system of continuing education still forms the basis of modern pedagogy today. In modern pedagogical and psychological research of recent years, the problem of developing the creative competence of Future Educators has been studied in a wide range, and its scientific and theoretical foundations have been formed. Today, the state and society set the task of continuous professional development for future educators. Such a development process is primarily organized on the basis of the requirements of an acmeological approach. This in turn presupposes specialists who are creative, independent thinkers, able to solve life situations on the basis of a strict approach, who deeply occupy professional competencies. Educational programs that will be based on the organization of such a pedagogical process should be created on the principle of an acmeological approach. To solve the problem of insufficient creative competence of future educators, it is necessary to use active educational technologies in the teaching of subjects, to organize classes with interest and meaning, using unconventional forms, methods and tools. Only then can students achieve high creative activity and ensure successful studies in the field of creativity. This article covers various aspects of training on the basis of an acmeological approach and the development of the creative abilities of specialists taking into account their professional development.